Neurocysticercosis: clinical presentations, serology and radiological findings: experience in a teaching institution - Arora, Balvinder S.; Dhamija, Kamakshi (International Journal of Research in Medical Sciences, 2016)
Background: The objective of the study was to study the clinical presentations, serological evidence and radiological findings in cases of neurocysticercosis in a teaching institution with attached tertiary care hospital settings. Methods: A total of 60 paediatric age group patients were enrolled in the study and their clinical presentations, serological profile and radiological findings were recorded. Study data was evaluated in a retrospective analysis of the descriptive hospital based observational study conducted at Safdarjang hospital (SJ) hospital, New Delhi. Results: Generalised seizures were the most predominant clinical presentation in 28/60 cases (47%). Majority of the patients had single lesions in parietal lobe in CT head. 90% of the patients showed perilesional oedema on CT scan. Differences in IgG positivity rate in the various age groups were not significant either for serum or CSF - the p values were 0.67 & 0.052 respectively. Seropositivity was also not significantly associated with presence of active NCC lesions on CT (p= 0.254). In further analysis, diet was not found to have any significant influence on either seropositivity (p value=0.673) or on the pattern of presentation on CT (p=0.260). NBM-It is disappointing to know that only 20% urban 45%rural is aware of 8 hours NBM before surgery. Conclusions: Observations suggest there is variability in the clinical, serological and radiological presentation of neurocysticercosis when compared with standard criteria.